The shadow teaching scheme for children with autism and attention deficit-hyperactivity disorder in regular schools - Manansala, Maryola A. (Education quarterly.)
This study aimed to determine the place of shadow teaching in the education and training of children with special needs (CSN). This study reveals that shadow and regular teachers agree that shadow teaching helps improve the academic performance, psychological skills, and independence capabilities of CSN. Shadow teachers believe that their most important responsibility is team working with regular teachers, whereas regular teachers think that their most important task is curriculum planning.